Analisis Sistem Pendukung Keputusan Pemilihan Merek Pasta Gigi Terbaik Menggunakan Metode SERVQUAL dan ORESTE - Rahma Dhea Safitri; Anjar Wanto (BEES: Bulletin of Electrical and Electronics Engineering, 2025)
This study aims to address the problem of selecting the best toothpaste brand by developing a decision support system using a combination of the SERVQUAL and ORESTE methods. The problem raised is the difficulty consumers face in determining the most suitable product based on service quality. The SERVQUAL method is used to measure performance based on five dimensions of service quality, while ORESTE is used to rank alternatives without explicit weights. The system is implemented in the form of a data-driven evaluation model designed to mimic real-world conditions. The data reflects the perceived and expected values of several toothpaste brands, with the difference (GAP) calculated and processed using the ORESTE method to generate rankings. The results show that the Ciptadent brand received the highest preference with the lowest total ranking (6), followed by Oral-B and Colgate. The integration of these two methods enables a systematic and objective evaluation of overall service quality and can be used to support accurate consumer decision-making.